130 PREDICTORS OF DRIVING STATUS IN OLDER IRISH ADULTS ATTENDING A GERIATRIC OUTPATIENT SERVICE. (18th November 2021) - Moloney, K; O'Flaherty, N; Ahmad, R; Laird, E; Hughes, C; McNulty, H; Ward, M; Strain, J J; Molloy, A M; Cunningham, C; McCarroll, K
Abstract: Background: The main mode of transportation in Ireland remains travel by car. Transport mobility is important for older adults in accessing shops, healthcare, services, community and in maintaining relationships. Cessation of driving is associated with negative effects on mental health, loneliness and physical health. We aimed to explore factors associated with driving status in older adults living in an urban environment. Methods: Study included adults aged greater than 65 years attending a geriatric outpatient service in an urban environment and recruited as part of the TUDA (Trinity Ulster, Department of Agriculture) study. We excluded those with a MMSE (Mini-Mental State Exam) less than 24 as we aimed to include only non-dementia patients. Physical frailty was measured with the Timed Up and Go (TUG) and depression with the Center for Epidemiological Studies Depression scale (CES-D). Factors associated with driving status were explored in multinomial regression models. Results: 1978 adults, mean age 77.7 ± 7.1 years, 76.0% were female. 35.5% were current drivers but this differed by age category 45.9% (65–75 years), 25% (75–85 years) and 12.5% (85+ years). 28.1% were past drivers. Positive independent predictors of current driving were younger age (P < 0.001), male gender (P < 0.001), married status (P = 0.01), higher socioeconomic status (P < 0.0001) while negative predictors included physical frailty (TUG, P < 0.001), visual impairment (P = 0.01), stroke (P < 0.001), depression (P < 0.001) and self reported loneliness (P = 0.01). Conclusion: One third of patients attending a geriatric outpatients in an urban environment were currently driving which is much lower than in the general older Irish population. However, our study included frail adults living in more deprived socioeconomic areas and had a high proportion of females who had never learned to drive. Furthermore, access to urban public transport may be a factor. Non-drivers were more likely to have depression and report loneliness independent of other factors highlighting its negative impact.